Prehospital Transfusion of Low-Titer O + Whole Blood for Severe Maternal Hemorrhage: A Case Report. (3rd July 2020) - Newberry, Ryan; Winckler, C. J.; Luellwitz, Ryan; Greebon, Leslie; Xenakis, Elly; Bullock, William; Stringfellow, Michael; Mapp, Julian
Abstract: Introduction: Beginning in 2017, multiple stakeholders within the Southwest Texas Regional Advisory Council for Trauma collaborated to incorporate cold-stored low-titer O RhD-positive whole blood (LTO + WB) into all phases of their trauma system, including the prehospital phase of care. Although the program was initially focused on trauma resuscitation, it was expanded to included non-traumatic hemorrhagic shock patients that may benefit from whole blood resuscitation. Case Report: We report the case of a patient with severe maternal hemorrhage secondary to placenta accreta who received a prehospital transfusion of LTO + WB. We believe this to be the first reported case of post-partum hemorrhage resuscitated out of hospital with whole blood. Discussion: This case highlights the potential benefits of a prehospital whole blood program as well as the controversy surrounding a LTO + WB program that includes females of childbearing age.